Sound change across generations: evidence from North Russia - Krasovitsky, A (2011)
The focus of the study is ongoing sound change observed through variation across several generations of speakers. Until recently there has been a consensus that a large number of North Russian dialects systematically discriminate low and mid vowels in unstressed syllables.Recent fieldwork in one of the North Russian rural communities has shown that the discrimination model may hold only for some of the older speakers whereas in the majority of idiolects, particularly within middle and younger generation, we find numerous instances of vowel neutralization. One example is the neutralization of low and mid vowels, /a/ and /o/, in unstressed syllables. We find three types of the idiolects which present three successive stages of the loss phonological distinction between /o/ and /a/ in unstressed syllables. Type A consistently discriminates between low and mid phonemes in unstressed syllables (some of the older speakers). The opposite of this is Type C with /o/ and /a/ systematically neutralized in [?] or [?] (middle and younger generation). Multiple choices in type B, typical for the majority of the older speakers of the dialect, reveal a competition of the discrimination and neutralization pattern found in A and C accordingly.